Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10826-011-9472-1
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Strategic Community Engagement in Recruiting African American Youth & Families for Clinical Research

Abstract: We present baseline data and describe the utility of a community engaged, culturally relevant approach to recruiting African American youth and families for phase I of The AAKOMA Project. The AAKOMA Project is a two phase treatment development study to improve mental health service use among depressed African American youth. We completed capacity building activities using a community engaged framework and Community Based Participatory Research (CBPR) methods. Replicating the (Alvarez et al. in West J Nurs Res … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…7,11,12 Previous research has primarily focused on examining associations between recruitment strategies and enrollment rates in health promotion programs [13][14][15] and understanding the use of faith-based and community partnerships in recruitment. 7,[11][12][13] Results suggest that recruitment medium may be as-…”
Section: Recruitment Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11,12 Previous research has primarily focused on examining associations between recruitment strategies and enrollment rates in health promotion programs [13][14][15] and understanding the use of faith-based and community partnerships in recruitment. 7,[11][12][13] Results suggest that recruitment medium may be as-…”
Section: Recruitment Proceduresmentioning
confidence: 99%
“…7,[10][11][12] Examples of community partnerships used previously include the use of community advisory boards, community liaisons, and collaboration with local organizations such as churches and clinics. 6,11,13,14 In addition to providing a better understanding of important sociocultural values, community partnerships increase participant sociated with enrollment rates and recruitment yield, with communitybased sources and partnerships being most effective. 13 Although past research has examined the success of different types of recruitment strategies, direct comparisons between sociocultural and non-sociocultural recruitment mediums have not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“….g., Allison et al, 1999; Cutrona, et al, 2000; Gaylord-Harden, Cunningham, & Zelencik, 2011; Cooley-Quille & Lorion, 1999), there is still a possibility that self-selection in our sample may result in it not being fully representative. In addition to the noted difficulty in engaging low-income African American populations (Breland-Noble, Bell, & Poole, 2012), it is possible that this response rate resulted from the requirement that participants return both assent and parental consent forms, low attendance of the students, or even suspicions of clinical research being conducted in African American communities (Allison et al, 1999). Thus, future research in these communities should strive to use community-based participatory research (CBPR) strategies in order to increase recruitment and reduce bias.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that high-risk, low-income minority samples, such as this one, are difficult to engage in research due to the levels of disorganization and stress in their lives, resulting in barriers such as time constraints due to work schedules, lack of childcare, or general life crises (Allison et al, 1999; Breland-Noble, Bell, Burriss, & Poole, 2012). …”
Section: Methodsmentioning
confidence: 99%